1994
DOI: 10.1136/bjo.78.7.542
|View full text |Cite
|
Sign up to set email alerts
|

Relation between iridopathy and retinopathy in diabetes.

Abstract: In order to assess the relation between diabetic iridopathy (DI) and retinopathy (DR), 225 eyes of 117 diabetics with clear media were evaluated. Each patient underwent iris and retinal fluorescein angiography, which was used to classify DI and DR. DI was classified as: absence of DI; non-proliferative DI; proliferative DI; neovascular glaucoma. DR was classified as: absence of DR; background DR; pre-proliferative DR; proliferative DR. The sensitivity of iris fluorescein angiography in assessing DR was 44 5%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 23 publications
2
25
1
Order By: Relevance
“…The amount of leakage was related to the severity of MCP. Correlation of the grade of retinopathy and iridopathy has been reported in other diseases [2]. Unfortunately, we do not have predisease angiograms or larger series of control angiograms to compare our findings in a longitudinal study.…”
Section: Filling Defectsmentioning
confidence: 67%
“…The amount of leakage was related to the severity of MCP. Correlation of the grade of retinopathy and iridopathy has been reported in other diseases [2]. Unfortunately, we do not have predisease angiograms or larger series of control angiograms to compare our findings in a longitudinal study.…”
Section: Filling Defectsmentioning
confidence: 67%
“…In this study, retinal photocoagulation had no influence on high laser flare intensity, because laser photometry was performed 3 months after retinal photocoagulation. The relationship between iridopathy and retinopathy in diabetes has already been assessed [21]. Advanced iris changes on iris angiography significantly correlated with the presence of PDR.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, retinopathies with grade III and IV dye leakage were found to be actively proliferative. Dye leakage from the iris is an indicator of pronounced PDR [21]. In other words, high laser flare intensity suggests advanced bloodocular barrier disruption, iridopathy and retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Its value has been demonstrated especially in the vaso-occlusive disorders, wherever IFA is able to show neovascular tufts and guide the laser treatment in an effort to avoid neovascular glaucoma development. 1 2 Moreover, it is highly recommended in diabetic patients who need cataract surgery or vitrectomy.3 4 Nevertheless, IFA often fails to demonstrate the iris vascular pattern particularly in cases presenting heavily pigmented iris or conspicuous leakage.…”
mentioning
confidence: 99%
“…The diabetic retinopathy level was graded in a masked fashion according to the Wisconsin Epidemiologic Study of Diabetic Retinopathy,5 by means of ophthalmoscopy, standard fundus photography, and fluorescein angiography. In particular, we considered 11 patients with non-proliferative diabetic retinopathy (NPDR) (level 1-3), 13 patients with pre-proliferative diabetic retinopathy (PPDR) (level [4][5], and 12 patients with proliferative diabetic retinopathy (PDR) (level 6 5-7).…”
mentioning
confidence: 99%